DEVELOPMENT OF TECHNICAL CREATIVE ABILITIES IN STUDENTS THROUGH GEOMETRIC-GRAPHIC DESIGN WORKS - Abdurakhmanov Sh.; Butaev A.; Zakirov V. (Galaxy International Interdisciplinary Research Journal, 2022)
The scientific article is devoted to the development of technical creative abilities of students with the help of geometric-graphic design exercises in drawing classes, and the authors' pedagogical experiences in this direction are described in detail.